ANALISIS PERUBAHAN PENUTUPAN LAHAN HUTAN LINDUNG SUNGAI PULAI PROVINSI KEPULAUAN RIAU - Wienda Lestari Br. Gurusinga; Dimas Nugraha Pamungkas; Ridwan Manda Putra; Defri Yoza (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2023)
Land cover in forested area has changed rapidly. This study aims to determine the existing conditions and changes in land cover in the Sungai Pulai Protection Forest Area on Bintan Island, Riau Islands in the last 13 (thirteen) years from 2009 – 2022 along with the contributing factors. This research was conducted using survey and interview methods. Data analysis consisted of map analysis and descriptive analysis. The results showed that there were 9 (nine) classes of land cover in the Sungai Pulai Protected Forest area in the period 2009 – 2022, namely secondary forest, shrubs, plantations, dry land agriculture, dry land agriculture mixed with shrubs, open land, bodies of water, settlements and airport. The most extensive land cover in the Sungai Pulai Protection Forest is palm oil plantations covering an area of 241.51 ha (32.12%), followed by dryland agriculture mixed with shrubs covering an area of 221.19 ha (29.42%), settlements covering 120.18 ha (15.99%), and dryland agriculture area of 71.99 ha (9.58%). Changes in land cover are caused by community activities in forest areas including agriculture, settlements, illegal logging, forest fires, and palm oil plantations by companies. The increase in these activities was caused by weak law enforcement, increasing population, economic needs of the community and lack of public awareness about the importance of forest functions.